(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Tourism managers are responsible for managing the day-to-day operations of their organization’s tourism services. They oversee all aspects of the business, from marketing and sales to customer service and employee training.